How political parties' issue ownerships reduce to spatial proximity. Issue 6 (18th September 2020) - Seeberg, Henrik Bech
Abstract: Scholarly interest in issue ownership is growing rapidly. Although originally introduced as a competence-oriented, alternative concept to the predominantly spatial understanding of voting and party behaviour, parties' policy positions are an inescapable aspect of issue ownership. Using data for multiple issues in several countries over time, this article shows that the party with issue ownership sides with the median voter. A party earns issue ownership by taking up a position as close to as many voters as possible. Moreover, the analysis indicates that a party's issue emphasis only matters to issue ownership insofar as it is used as a device to make its position credible to voters. Hence, to have issue ownership is to have a credible position, and in that sense, issue ownership has less added theoretical value to spatial proximity than previous literature suggests.